The Modern Gothic in Twentieth Century - Khabibova Shakhnoza Ismatullaevna (Genius Journals, 2021)
The works secured to by the umbrella term “Gothic” are so shifted in fashion, thematic interests, and account impacts that an overarching definition gets to be tricky and even undesirable. The modern Gothic, drawing on an as of now divided and heterogenic artistic tradition, is less a sort than a minimal sort of composing that resuscitates more seasoned repulsions and formulas and channels them through the reverberate chambers of the nowadays distraction with the social esteem of transgresses writing
Keywords: Gothic; modern writing; post-millennial writing; class